How Financial Literacy Impacts Financial Well-Being: The Influence of Financial and Technical Efficacy - Chaity, Naznin Sultana; Kabir, Shahriar Bin; Akhter, Parul; Bokhari, Rifat Parveen (International Journal of Economics and Financial Issues, 2024)
The fundamental human resource that influences financial well-being is financial literacy. People are more likely to save and invest if they understand the time value of money, credit, insurance, and investments. Having a sound financial understanding lessens stress and increases financial well-being. This study used a structured survey questionnaire and back-translated it into Bangla to ease readability for the respondents. Four hundred thirty-five invitations were sent mainly to the Dhaka city dwellers’ and only 253 complete responses were retained for analysis. Partial least squares structural equation modeling (PLS-SEM) is used to assess the intercorrelations and validate the measurement model among the constructs (financial attitude, behavior, knowledge, self-efficacy, technological self-efficacy, and financial well-being) using SmartPLS version 4. The result found a full mediation effect among financial behavior, financial self-efficacy, and financial well-being. Partial mediation effects are found among financial attitudes toward financial self-efficacy, technological self-efficacy, and financial well-being.